2001
DOI: 10.1128/iai.69.4.2569-2579.2001
|View full text |Cite
|
Sign up to set email alerts
|

HtrA Homologue of Legionella pneumophila : an Indispensable Element for Intracellular Infection of Mammalian but Not Protozoan Cells

Abstract: Legionella pneumophila replicates within alveolar macrophages, and possibly, alveolar epithelial cells and also within protozoa in the aquatic environment. Here we characterize an L. pneumophila mutant defective in the HtrA/DegP stress-induced protease/chaperone homologue and show that HtrA is indispensable for intracellular replication within mammalian macrophages and alveolar epithelial cells and for intrapulmonary replication in A/J mice. Importantly, amino acid substitutions of two conserved residues in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 47 publications
9
90
0
Order By: Relevance
“…Expression of htrA is upregulated in S. Typhimurium with macrophages (Eriksson et al, 2003;Everest et al, 1995) and other pathogens that reside within a phagosome such as Yersinia enterocolitica (Yamamoto et al, 1997) and Legionella pneumophila (Pedersen et al, 2001). However, there is almost no similarity between the htrA promoter regions of these bacteria and we were unable to locate counterparts of the S. Typhimurium htrA promoters in these promoter regions.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Expression of htrA is upregulated in S. Typhimurium with macrophages (Eriksson et al, 2003;Everest et al, 1995) and other pathogens that reside within a phagosome such as Yersinia enterocolitica (Yamamoto et al, 1997) and Legionella pneumophila (Pedersen et al, 2001). However, there is almost no similarity between the htrA promoter regions of these bacteria and we were unable to locate counterparts of the S. Typhimurium htrA promoters in these promoter regions.…”
Section: Discussionmentioning
confidence: 43%
“…This is not the case in Salmonella, but S. Typhimurium htrA mutants exhibit increased sensitivity to killing by reactive oxygen species and reduced survival and/or replication within macrophages (Baumler et al, 1994;Humphreys et al, 1999;Johnson et al, 1991), and are highly attenuated in the murine model of systemic Salmonella infection (Chatfield et al, 1992;Humphreys et al, 1999). Since the seminal studies in Salmonella, HtrA has been found to play a role in the virulence of a wide range of Gram-negative and Grampositive bacterial pathogens (Bringer et al, 2005;Cortes et al, 2002;Humphreys et al, 1999;Ibrahim et al, 2004;Johnson et al, 1991;Jones et al, 2001;Pallen & Wren, 1997;Pedersen et al, 2001;Rigoulay et al, 2005;Williams et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, another thiol-disulfide oxidoreductase (ResA) involved in cytochrome C synthesis (85-88), several predicted metabolic or substratebinding proteins, such as amino acid-binding protein Lpg0498, polysaccharide deacetylase Lpg0633, amine oxidase Lpg1153, hydroxymethylglutaryl CoA-reductase Lpg2052, G3P ABC transporter substrate-binding protein UgpB, were detected as omap E-on. Among the remaining 16 E-or PE-up proteins, five belonged to the functional categories "protein fate" (E-up: DsbA, HtrA, LolA, PE-up: metallopeptidase PepO, carboxyl terminal protease Lpg0499) (79,83,89,90), two to "pathogenesis" (E-up: Lpg1585, PE-up: EnhA/ Lpg2641) (91), two to "transport and binding" (PE-up: arginine ABC transporter substrate-binding protein ArtJ (92), E-up: sugar ABC transporter substrate-binding protein Lpg0184), and one to "cellular processes" (PE-up: carbonic anhydrase Lpg2500) (Fig. 4, supplemental Fig.…”
Section: Overview Of L Pneumophila E and Pe Soluble Whole Cellmentioning
confidence: 99%
“…Bacteria were added to macrophages and the infection was synchronized by centrifugation. At 20 minutes and 80 minutes post-infection cell monolayers were washed three times with PBS and fixed as described below [225,226]. Statistics.…”
Section: Rab1b Inhibition Results In Increased Acidification Of the Lmentioning
confidence: 99%
“…E. coli was cultivated at 37°C in Luria-Bertani (LB) broth (Difco) supplemented with 50µg/mL carbenicillin. L. pneumophila AA100, a clinical isolate containing pMIP-GFP, was grown on BCYE agar plates for 3 days at 37°C prior to macrophage infection [224][225][226]. The pGEN222::mCherry plasmid was generated by replacing the EGFP gene from pGEN222 with the mCherry gene using…”
Section: Rab1b Inhibition Results In Increased Acidification Of the Lmentioning
confidence: 99%